Case Study : MYR Construction Sdn. Bhd / Muhammad Hafizzullah Juha Seman - Juha Seman, Muhammad Hafizzullah (2020)
MYR Construction Sdn Bhd is a production and services business that provide the services in designing the furniture for government and private office, manufacturing various types of furniture for educational institute, supply interior decoration furniture for home and office in contract and supply furniture for government and private department. The problem faced by this company are they have a lot of leftover chipboard that are unorganized but still useful and can be used or other purpose and another problem is the time consuming to transfer design from designer computer at the office to CNC Boring Machine as they do not have any program that directly transfer the design to the machine. Therefore, this study will help this company to overcome that problems.